STUDY OF THE INFLUENCE OF MIXER WORKING BODY GEOMETRY ON THE KINETICS OF BULK MATERIAL MIXING - STADNIK, MYKOLA; SOLONA, OLENA; BURLAKA, SERHIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article examines the influence of the geometry of mixer working bodies on the kinetics of the bulk material mixing process. Mixing is one of the key technological processes in many industrial sectors, including the food, pharmaceutical, chemical, and construction industries. High-quality mixing ensures the uniformity of the final product, directly affecting its consumer and operational characteristics.An analysis of various types of mixing elements, including blade, ribbon, screw, and rotor-pulsation systems, was conducted. Particular attention was paid to their structural features, such as shape, size, inclination angle, and positioning within the mixing chamber. It was determined that the kinetics of mixing largely depend on the interaction between bulk material particles and the working bodies, as well as on aerodynamic and mechanical factors influencing particle movement during the mixing process.The study employed mathematical modeling methods and experimental analysis. Numerical simulations of particle motion dynamics were performed using the Discrete Element Method (DEM), allowing for the assessment of particle distribution uniformity within the mixing volume. Additionally, experimental tests of mixers with different designs were conducted to verify the theoretical results.The research findings indicate that modifying the geometry of the mixer’s working bodies can significantly impact mixing quality, process speed, and energy consumption levels. Optimizing the shape and arrangement of mixing elements improves mixture homogeneity, reduces mixing time, and decreases mechanical stress on equipment.The obtained results can be utilized for the modernization of industrial mixers to enhance their performance, reduce energy consumption, and improve the final product’s characteristics. In particular, the proposed recommendations may be applied in the design of new mixing systems and in the improvement of existing technological lines.This study is relevant in the context of developing innovative mixing technologies and increasing the efficiency of production processes across various industries. Future research may focus on a more detailed investigation of the influence of the physical and mechanical properties of bulk materials on mixing kinetics, as well as on the development of new structural solutions to improve mixing uniformity and reduce wear on mixing elements.
Keywords: analysis; vibration; mixing; velocity projection; bulk medium; frequency; mixture; vibration velocity